Анималистические гротески в фольклоре и литературе славянских народов как художественный антидепрессант и релевантный элемент культурной грамотности - Niekraszewicz-Karotkaja, Żanna (Studia Rossica Posnaniensia, 2023)
Songs with animalistic motifs are widely represented in the traditional culture of Slavic peoples. Songs with bird motifs clearly predominate, as most of them were originally connected with the archaic ritual of the bird wedding. In the course of their centuries of use, their erotic context has been reduced, and their social and didactic motifs have been strengthened. Embodied primarily in the form of grotesques (Czesław Hernas), these songs became an essential element of the cultural literacy (Eric Donald Hirsch) of the people and formed the basis of ethnopedagogy. The playful character and life-like plot collisions played a role of a peculiar psychotherapeutic means, which is confirmed by the reviews of ethnographers, as well as writers, who processed the folklore plots. In the culture of the Slavic peoples of the new time, the songs with bird motifs were most widespread, although the ritual of a bird wedding survived only among the Sorbs from Lusatia. Animalistic grotesques contributed to the socialization of a person, their awareness of themselves within various models of collective identity. This is why such poems and songs are especially relevant in the sphere of modern recreational culture, including in the field of preschool pedagogy.